The Influence of Good Corporate Governance Principles and Organizational Culture on the Financial Performance of Village Credit Institutions - Nyoman Dewi Ayu Ratih Arya Dewanti; I Gde Ary Wirajaya (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to examine the effect of applying the principles of good governance and organizational culture on financial performance. This research was conducted at the Village Credit Institution (LPD) in South Denpasar Subdistrict. The sampling method uses saturated sampling by involving 11 LPD in South Denpasar Subdistrict. The data collection method used is by distributing questionnaires. The analysis technique used is multiple linear regression. The results of this study indicate that transparency, accountability, responsibility, independence, justice and organizational culture have a positive effect on financial performance.